Severe Leukoplakia of the Vagina and Cervix Successfully Treated with Intravaginal Application of Topical Glucocorticoids - Condic, M; Mustea, A; Ralser, DJ; Wenzel, J; Braegelmann, C (Archives of Clinical and Medical Case Reports, 2022)
Leukoplakia of the vagina and cervix can hide (pre)malignant lesions or be caused by them, so biopsy and treatment is mandatory. Here we present a rare case of severe leukoplakia of the vagina and the cervix due to a chronic inflammatory reaction, which was successfully treated with intravaginal application of budesonide foam. In vulvar lesions, topical glucocorticoids are first line treatment, whereas intravaginal application is rare and pharmaceutical market lacks products for this indication. We describe a unique, well tolerated and successful treatment of chronic inflammatory reactions of the vagina and cervix resulting in quick and complete remission.